Yeast identification in grape juice concentrates from Argentina - Combina, Mariana; Daguerre, Claire; Massera, Ariel Fernando; Mercado, Laura Analia; Sturm, Maria Elena; Ganga, M. Angélica; Martínez, Claudio (Wiley, 2021)
Aims: The purpose of this study was to identify yeast species present in spoiled and unspoiled grape juice concentrates from Argentine industries. Methods and Results: Osmophilic and osmotolerant yeasts were isolated from spoiled – visually effervescent – and unspoiled – without any visible damage – grape juice concentrates by the spread‐plate technique in two culture media. Yeast identification was done by classical and molecular methods. Zygosaccharomyces rouxii was the only species isolated from spoiled grape juice concentrates. In unspoiled samples, five different species were identified: Z. rouxii was isolated at a higher frequency, followed in decreasing order by Saccharomyces cerevisiae, Schizosaccharomyces pombe, Pichia anomala and Kluyveromyces delphensis. Conclusions: Yeasts isolated from grape juice concentrates were characterized by a limited taxonomic diversity, where Z. rouxii was the main species isolated. Significance and Impact of the Study: Grape production in Argentina is mainly devoted to the industry where wine and grape juice concentrates represent major types of commercial products. Little information on common yeast contaminants is available for grape juice concentrates. This study constitutes the first report of osmophilic yeast species present in spoiled and unspoiled grape juice concentrates elaborated in Argentina.